Answer:
C 152
Step-by-step explanation:
Beacuse it is. Hope that helps
I would say true. Hope this helps :)
Answer:
19
Step-by-step explanation:
Difference between one end point and mid point
= 27 - 23 = 4
Other endpoint = 23 - 4 = 19
Answer:
x⁶ +30x⁵ +375x⁴ +2500x³ +9375x² +18750x +15625
Step-by-step explanation:
The expansion is the sum of C(6, k)·x^(6-k)·5^k for k=0–6, where ...
... C(6, k) = 6!/(k!(6-k)!)
For k = 0–6, C(6, k) = {1, 6, 15, 20, 15, 6, 1}
Then the expansion is ...
... x⁶ +6·5¹·x⁵ +15·5²·x⁴ +20·5³·x³ +15·5⁴·x² +6·5⁵·x +5⁶